Alcohol consumption as a preventive factor for developing rheumatoid arthritis: a dose-response meta-analysis of prospective studies. Issue 11 (29th July 2013) - Jin, Zhichao; Xiang, Chun; Cai, Qing; Wei, Xin; He, Jia
Abstract : Objective: To summarise the evidence regarding the dose-response association between alcohol consumption and risk of rheumatoid arthritis (RA). Method: Studies were identified from search of MEDLINE, Embase and Web of Science databases between 1 January 1946 and 10 April 2013, and from review of the conference abstracts and the reference lists of retrieved articles. Prospective studies that reported relative risks (RRs) with 95% CIs for the association between alcohol consumption and the risk of RA were included. Results from individual studies were pooled using a dose-response meta-analysis. Results: Up to 10 April 2013, 8 prospective studies contained 195 029 participants and 1878 RA cases were included. The results indicated that low to moderate alcohol consumption yielded a preventive effect on RA development (RR: 0.86; 95% CI 0.78 to 0.94), and provided some evidence of a non-linear relationship between alcohol consumption and risk of RA. Dose-response meta-analysis of the study data revealed that compared with that for no alcohol consumption, the adjusted RR was 0.93 (95% CI 0.88 to 0.98) for 3 g/day of alcohol consumption, 0.86 (95% CI 0.76 to 0.97) for 9 g/day, 0.88 (95% CI 0.78 to 0.99) for 12 g/day, 0.91 (95% CI 0.81 to 1.03) for 15 g/day, and 1.28 (95% CI 0.94 to 1.73) for 30 g/day. Subgroup analysis indicated that women who had low to moderate alcohol consumption had a 19% reduction in RA risk. Regardless of sex, a consistent low to moderate alcohol consumption for a period of at least 10 years was found to have a 17% reduction in RA risk. Conclusions: Low to moderate alcohol consumption inversely associated with the development of RA in a manner that appears to be dose-dependent, time-dependent and sex-dependent. Large prospective studies that investigate gene-environment interactions are required to further clarify the aetiology of RA.